2007
DOI: 10.1074/jbc.m701074200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Native Protein C Inhibitor Provides Insight into Its Multiple Functions

Abstract: Protein C inhibitor (PCI) is a multifunctional serpin with wide ranging protease inhibitory functions, unique cofactor binding activities, and potential non-inhibitory functions akin to the hormone-transporting serpins. To gain insight into the molecular mechanisms utilized by PCI we developed a robust expression system in Escherichia coli and solved the crystal structure of PCI in its native state. The five monomers obtained from our two crystal forms provide an NMR-like ensemble revealing regions of inherent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…As serpins are known to adopt different conformations, models of protein C inhibitor Li et al, 2007) and thyroxine-binding globulin (Zhou et al, 2006), representing one relaxed and two stressed serpin conformations ($47% sequence identity; PDB entries 1lq8, 2ce0 and 2hi9), were selected as search models. A clear single solution was obtained from a search using PDB entry 1lq8 as the model with one copy of molecule in the asymmetric unit, indicating a solvent content of $60%.…”
Section: Resultsmentioning
confidence: 99%
“…As serpins are known to adopt different conformations, models of protein C inhibitor Li et al, 2007) and thyroxine-binding globulin (Zhou et al, 2006), representing one relaxed and two stressed serpin conformations ($47% sequence identity; PDB entries 1lq8, 2ce0 and 2hi9), were selected as search models. A clear single solution was obtained from a search using PDB entry 1lq8 as the model with one copy of molecule in the asymmetric unit, indicating a solvent content of $60%.…”
Section: Resultsmentioning
confidence: 99%
“…1B). Although it appears as if the H helix is the principal GAG binding site, mutation of the basic residues on helix H only marginally affects heparin affinity or heparin acceleration of protease inhibition (18,21,22). In fact, it takes at least three simultaneous mutations to see an appreciable detrimental effect and removal of all four positively charged residues to knock out heparin acceleration altogether.…”
Section: Protein C Inhibitor (Pci)mentioning
confidence: 99%
“…In fact, it takes at least three simultaneous mutations to see an appreciable detrimental effect and removal of all four positively charged residues to knock out heparin acceleration altogether. We have recently shown that the minimum heparin length that fully occupies the heparin binding site of PCI is an octasaccharide, which fits neatly along the length of helix H (22) (Fig. 1C).…”
Section: Protein C Inhibitor (Pci)mentioning
confidence: 99%
See 2 more Smart Citations